Host–symbiont plasticity in the upside-down jellyfish Cassiopea xamachana: strobilation across symbiont genera - Sharp, Victoria; Kerwin, Allison H.; Mammone, Marta; Avila-Magana, Viridiana; Turnham, Kira; Ohdera, Aki; LaJeunesse, Todd; Medina, Mónica (Frontiers in Ecology and Evolution, 2024)
Introduction In the upside-down jellyfish, Cassiopea xamachana (Cnidaria: Scyphozoa), the establishment of photosymbiosis with dinoflagellates (family Symbiodiniaceae) is necessary for the sessile polyp to undergo metamorphosis (strobilation) into a free-swimming adult. C. xamachana has the capacity to associate with a wide variety of dinoflagellate species and representatives of divergent genera. While some studies have looked at the successful induction of symbiosis, none to date have examined the lasting effect of diverse symbiont taxa on host survivorship and development, which is needed to assess the fitness costs of such symbioses. Methods Our study exposes C. xamachana polyps to 22 different cultured Symbiodinaceae strains representing 13 species from 5 genera. We analyzed the time to strobilation, the number of ephyra (juvenile medusa) produced, and the proportion of ephyra that died prematurely. Results Here we show that C. xamachana strobilation can be induced by nearly each symbiodinacean strain we tested, with the exception of free-living species (i.e., unknown to establish symbiosis with any other marine host). Additionally, ephyrae did not display morphological variation or survivorship differences with varying symbionts. However, we observed intraspecific variation in time to induce strobilation with different cultured dinoflagellate strains. Discussion This work expands the known symbiont species that can form stable mutualisms with C. xamachana, primarily in the genera Symbiodinium and Breviolum. Additionally, we provide evidence of differences in ability of cultured symbiodiniaceans to establish symbiosis with a host, which suggests population-level differences in dinoflagellate cultures impact their symbiosis success. By utilizing an animal like C. xamachana with flexible symbiont uptake, we are able to explore how symbiont diversity can influence the timing and success of symbiosis-driven development.